Strategi KOIN NU Sebagai Kampanye Kesadaran Milenial Dalam Berzakat Dan Berinfaq - Intan Putri Nazila (Universitas Islam Darul 'ulum Lamongan, 2023)
The purpose of this study was to answer the problem formulation in the research system on the implementation of the KOIN NU program in LAZISNU Porong Sidoarjo, the strategy for implementing the KOIN NU program in Porong LAZISNU Sidoarjo Regency, and obstacles faced in the implementation of the program of the KOIN NU in LAZISNU Porong Sidoarjo Regency. This research is a qualitative research because it focuses on observations about human behavior. In addition, this study uses field research methods by going directly to the research location to obtain the data needed. The results of this study are that the system for implementing the Nahdlatul Ulama Infaq Movement (KOIN NU) program in LAZISNU Porong Sidoarjo Regency is divided into three parts, namely the fund collection system, fund management system, and fund distribution system. The strategy for implementing the Nahdlatul Ulama Infaq Movement (KOIN NU) program at LAZISNU Porong Sidoarjo Regency was carried out by conducting SOP formulation, activity planning, and evaluation. Factors supporting the KOIN NU movement are good resource management, good program management, and high public enthusiasm. Whereas the obstacles faced during the implementation of the Nahdlatul Ulama Infaq Movement (KOIN NU) program in LAZISNU Porong Sidoarjo Regency were a lack of human resources and the occurrence of internal problems in the organization